Rapid identification of Psathyrostachys huashanica Keng chromosomes in wheat background based on ND-FISH and SNP array methods - Jia-chuang LI; Jiao-jiao LI; Li ZHAO; Ji-xin ZHAO; Jun WU; Xin-hong CHEN; Li-yu ZHANG; Pu-hui DONG; Li-ming WANG; De-hui ZHAO; Chun-ping WANG; Yu-hui PANG (Journal of Integrative Agriculture, 2023)
Psathyrostachys huashanica Keng (2n=2x=14, NsNs) is regarded as a valuable wild relative species for common wheat cultivar improvement because of its abundant beneficial agronomic traits. However, although the development of many wheat–P. huashanica-derived lines provides a germplasm base for the transfer of excellent traits, the lag in the identification of P. huashanica chromosomes in the wheat background has limited the study of these lines. In this study, three novel nondenaturing fluorescence in situ hybridization (ND-FISH)-positive oligo probes were developed. Among them, HS-TZ3 and HS-TZ4 could specifically hybridize with P. huashanica chromosomes, mainly in the telomere area, and HS-CHTZ5 could hybridize with the chromosomal centromere area. We sequentially constructed a P. huashanica FISH karyotype and idiogram that helped identify the homologous groups of introduced P. huashanica chromosomes. In detail, 1Ns and 2Ns had opposite signals on the short and long arms, 3Ns, 4Ns, and 7Ns had superposed two-color signals, 5Ns and 6Ns had fluorescent signals only on their short arms, and 7Ns had signals on the intercalary of the long arm. In addition, we evaluated different ways to identify alien introgression lines by using low-density single nucleotide polymorphism (SNP) arrays and recommended the SNP homozygosity rate in each chromosome as a statistical pattern. The 15K SNP array is widely applicable for addition, substitution, and translocation lines, and the 40K SNP array is the most accurate for recognizing transposed intervals between wheat and alien chromosomes. Our research provided convenient methods to distinguish the homologous group of P. huashanica chromosomes in a common wheat background based on ND-FISH and SNP arrays, which is of great significance for efficiently identifying wheat–P. huashanica-derived lines and the further application of Ns chromosomes.